Nursing students' experiences with the objective structured clinical examination (OSCE): A qualitative study - Yosra Raziani; Ahmad Nazari; Sheno Raziani (Elsevier, 2022)
Background: Objective Structured Clinical Examinations (OSCEs) are widely applied in health communities to provide constructive feedback to students on their clinical skills. Despite the fact that OSCE offers a comprehensive, consistent, and standardized method for evaluating students' clinical learning skills, students are commonly unable to project their real knowledge that they are equipped with resulting in scoring errors. Objective: Investigating nursing students' views towards OSCE to reach a higher standard of clinical evaluation. Design: A qualitative, exploratory study. Methods: Final year nursing students who experienced OSCE was the target population, data were collected with semi-structured interviews. After 25 interviews, data saturation was achieved. The interviews were verbatim transcribed and analyzed according to qualitative content analysis based on Graneheim and Lundman method. To achieve trustworthiness, the methods proposed by Lincoln and Guba were used. Results: Two main themes emerged during data analysis were: 1- management problems, that includes 3 categories: 1) supervisor's behavior, 2) time management,3) facilities, and 2- educational problems including three categories of 1) simulation, 2) educational background, 3) question design which are key factors in conducting a more rational evaluation. Conclusion: Although OSCE is an accepted method of clinical evaluation, there are some drawbacks in both management and education that require attention. These results could be effective in improving clinical evaluation and educational programs. Using more student-centered methods in teaching and providing facilities to bring students to the real world of the profession can help them to improve their ability in clinical decision making.